2008
DOI: 10.4028/www.scientific.net/kem.375-376.102
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Performances, Mechanical Property and Microstructure of Ultra-Fine Grade Ti (C,N)-Based Cermets

Abstract: The two cutting tools obtained from ultra-fine grade Ti (C,N)-based cermets were tested in the dry cutting of a medium carbon steel (AISI1045). Microstructure and mechanical properties were studied. Wear mechanisms (mainly diffusion and oxidation) were investigated in detail and compared each other in order to better understand key aspects due to thermal wear mechanisms. Comparing tool A with B, under the adopted cutting conditions, the tool A has a better resistance to oxidation deformation in machining mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Thanks to outstanding red hardness, thermal stability and wear resistance, Ti(C,N)-based cermets have been utilized as cutting tool materials to substitute cemented carbides [ 1 , 2 , 3 ]. As a basic component of cermets, metal binder has been considered as the main factor influencing density, strength, and toughness [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to outstanding red hardness, thermal stability and wear resistance, Ti(C,N)-based cermets have been utilized as cutting tool materials to substitute cemented carbides [ 1 , 2 , 3 ]. As a basic component of cermets, metal binder has been considered as the main factor influencing density, strength, and toughness [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lu and Shen suggested that the incorporation of C in TiN lattice plays a positive role in the structural stability of TiC x N 1−x thin films, and this effect would be further enhanced by the formation of nanostructures [22]. TiC x N 1−x cermet modified with ultrafine-or nano-structures also exhibits an improved mechanical performance at ambient and elevated temperatures [23,24].…”
Section: Introductionmentioning
confidence: 99%